Analysis of the Effects of Tourism and Information and Communication Technology on Gross Regional Domestic Product in Priority Tourism Destination Provinces - Susanto, Rifqy Achmad; Shofwan (Journal of Development Economic and Social Studies, 2025)
Tourism is considered to have significant potential to drive Gross Regional Domestic Product (GRDP) and is a key focus in Indonesia's economic development strategy. In 2021, Indonesia's tourism ranking rose significantly from 44th to 32nd place in the Travel and Tourism Development Index (TTDI), surpassing Malaysia, Thailand, and Vietnam. However, according to the TTDI, Indonesia still faces weaknesses in tourism service infrastructure, socioeconomic resilience, and ICT readiness, which have hindered the even development of tourism and caused it to remain concentrated in Bali as the main contributor. This study aims to examine the impact of tourist expenditures, tourism productivity, the ICT index, and internet users on the GRDP of priority tourism destination provinces from 2018 to 2022. The study incorporates a COVID-19 dummy variable. A quantitative approach is employed, utilizing secondary data in panel data format. The cross-sectional sample includes 10 provinces, while the time-series sample is annual, spanning the period from 2018 to 2022. The findings reveal that tourist expenditures do not have a significant effect, while tourism productivity, the ICT index, and internet users have a positive and significant effect on GRDP in the priority tourism destination provinces during 2018–2022.